PENYULUHAN MENUJU GENERASI UNGGUL MEMBANGUN KESEHATAN MENTAL DAN ANTI BULLYING DI KALANGAN SEKOLAH MENENGAH ATAS KABUPATEN SUKABUMI - Umban Adi Jaya; Elis Yulianti; Mariati Tirta Wiyata; Zeffanya Rafhael Wijaya; Cucu Hodijah; Mulfi Sandi Yuda; Hilda Sri Rahayu; Galih Raspati (LPPM Universitas Bina Bangsa, 2024)
This service aims to increase awareness about building mental health and anti-bullying among students at the MA Al-Masthuriyah school, Sukabumi Regency, and also to provide a deeper understanding of the psychological impact of bullying. Through this outreach activity, it is hoped that school residents can become more responsive and proactive in preventing and overcoming cases of bullying. In this way, a safe and supportive learning environment can be created, allowing each individual to grow and develop optimally without fear of intimidation or unpleasant treatment. This service activity was carried out involving second grade students from the Department of Science, Social Sciences and Religion, reaching fifty people. This counseling is delivered in the form of interactive learning sessions with material covering, mental health, the importance of recognizing bullying, and preventing bullying; as well as in the form of playing guess the picture. Evaluation was carried out by distributing participant satisfaction questionnaires and then analyzed descriptively. The results show that the counseling towards a superior generation, building mental health and anti-bullying among high school students in Sukabumi Regency provides significant benefits for the students of MA Al-Masthuriyah school. Participants demonstrated increased understanding of Mental Health and Anti-Bullying. The majority of participants expressed satisfaction with the materials and counseling methods